2012
DOI: 10.1123/ijsnem.22.5.331
|View full text |Cite
|
Sign up to set email alerts
|

β-Alanine Improves Punch Force and Frequency in Amateur Boxers During a Simulated Contest

Abstract: The aim of this study was to test the hypothesis that ß-alanine supplementation improves punch power and frequency in amateur boxers during a simulated contest. Sixteen amateur boxers (each approximately 6 yr experience) were assigned to ß-alanine (n = 8; 1.5 g 4 times/d for 4 wk) or placebo supplementation (n = 8) after initially being assessed for baseline punch performance. Before and after the supplementation period, all boxers completed a simulated contest consisting of 3 × 3-min rounds (interspersed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 0 publications
0
66
0
Order By: Relevance
“…Some studies have failed to observe positive effects of BA on sports tasks, such as 400-m sprint running, 26 4-min 2728 and 1-h cycling time-trials. 29 In contrast, positive effects of BA have been shown in sports such as cycling (e.g., sprints, 4-km time-trial), 16,22 boxing, 17 soccer, 18 100-m and 200-m freestyle swimming timetrial 19 , 800-m running 20 and 2000-m rowing time-trials 21 . One possible explanation for the lack of positive results in some studies [26][27][28][29] may rely on the type of the exercise tests, which may have been too short or too long to properly stress the anaerobic glycolytic metabolism, and hence, induce H + accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have failed to observe positive effects of BA on sports tasks, such as 400-m sprint running, 26 4-min 2728 and 1-h cycling time-trials. 29 In contrast, positive effects of BA have been shown in sports such as cycling (e.g., sprints, 4-km time-trial), 16,22 boxing, 17 soccer, 18 100-m and 200-m freestyle swimming timetrial 19 , 800-m running 20 and 2000-m rowing time-trials 21 . One possible explanation for the lack of positive results in some studies [26][27][28][29] may rely on the type of the exercise tests, which may have been too short or too long to properly stress the anaerobic glycolytic metabolism, and hence, induce H + accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…10,14 It has been demonstrated that chronic BA supplementation (typically 4-10 weeks) may improve performance in a wide range of sports, especially in those characterized by a marked glycolytic demand. [15][16][17][18][19][20][21][22] Interestingly, BA appears to be as effective in highly-trained athletes as it is in physically active individuals. 23 Since BA has shown to be ergogenic in highly-trained athletes and in sports limited by acidosis, we hypothesized that BA could improve judo-related performance.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, an increasing number of studies have examined the potential ergogenic effects of BA across a range of exercise (Stout et al 2007, 2008; Sweeney et al 2010; Sale et al 2011; Jagim et al 2012; Smith-Ryan et al 2012) and sport-specific (Derave et al 2007; Baguet et al 2010; Van Thienen et al 2009; Bellinger et al 2012; Saunders et al 2012) tests. Despite some conflicting results, a recent meta-analysis concluded that BA is effective in improving exercise capacity (Hobson et al 2012), but only four studies have assessed the effects of BA supplementation on high-intensity intermittent exercise performance (Derave et al 2007; Donovan et al 2012; Saunders et al 2012; Smith-Ryan et al 2012), a model of exercise that is likely to be most sensitive in detecting the ergogenic effects of beta-alanine in comparison to continuous exercise. In contrast to some studies using continuous exercise protocols, our data convincingly demonstrate that BA alone (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the ergogenic effects of induced alkalosis have been more evident in intermittent than in continuous high-intensity exercises (Costill et al 1984). To our knowledge, however, only four studies have examined the effects of BA supplementation on high-intensity intermittent performance thus far (Derave et al 2007; Donovan et al 2012; Saunders et al 2012; Smith-Ryan et al 2012), with conflicting results being observed. Similarly, the two currently available studies on the combined effects of BA and SB have also used continuous exercise to assess performance (Sale et al 2011; Bellinger et al 2012), which may partially explain the lack of significant effects.…”
Section: Introductionmentioning
confidence: 99%
“…In psychometric, laboratory studies, this dilemma is known as a go/nogo task, and is performed without huge and acute fatigue, contrary to the conditions occurring during a real fight. No wonder that physiologists offer boxing contestants various pharmacological aids to improve their punching performance [5,24]. The other, non-directed way leading to enhanced psycho-physical abilities among boxers is based on comprehensive understanding of the physiological processes that occur during a boxing competition.…”
Section: Introductionmentioning
confidence: 99%